2022
DOI: 10.17559/tv-20210413092639
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of IGBT Single-Phase Bridge Arm Based on Fuzzy Logic Genetic Algorithm

Abstract: Aiming at the problem that single-phase rectifier transformation is prone to failure in the use of three-phase rectifier transformation, this paper introduces fuzzy logic genetic algorithm into the fault detection process of IGBT single-phase bridge arm structure. The algorithm mainly analyzes the DC side current in detail in the frequency domain to judge the fault of IGBT open circuit. In the fault diagnosis of single-phase bridge arm structure, the system circuit model is analyzed by sensors by using fuzzy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The Stackelberg leader-follower game model is leveraged to shape the government as the leader, with manufacturers, remanufacturers, and recyclers as followers. They concluded that government subsidies can incentivise recycling and remanufacturing, and that remanufacturing costs influence closed-loop supply chain decisions [14,15]. Study the impact of information sharing on multi-tier supply chain indices to generate different levels of performance [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The Stackelberg leader-follower game model is leveraged to shape the government as the leader, with manufacturers, remanufacturers, and recyclers as followers. They concluded that government subsidies can incentivise recycling and remanufacturing, and that remanufacturing costs influence closed-loop supply chain decisions [14,15]. Study the impact of information sharing on multi-tier supply chain indices to generate different levels of performance [16,17].…”
Section: Introductionmentioning
confidence: 99%